Examining the relationship between entrepreneurial education activity and entrepreneurship intention among Saudi university students: Academic performance as a mediator - Seraj, Abdullah Hamoud Ali (Edelweiss Applied Science and Technology, 2024)
This paper aims at investigating the direct impact of entrepreneurial educational activities on entrepreneurship intention, and academic performance among university students in Saudi Arabia, and the indirect impact between EEA and EI through AC. Data were collected from 488 university students representing 5 public Saudi universities. The structural equation modelling (PLS-SEM V.4) was used to examine the interrelationships between variables and to examine the research hypotheses. The SEM results showed that EEA have a positive direct impact on EI and AC, and proved a full mediating influence of AC on the relationship between EEA and EI among university students. These results may help decision-makers in higher education, in assisting in the formulation and planning of entrepreneurial educational activities, which help to create a flexible and adaptable society capable of meeting the demands of the modern world.